Communication—High Fidelity All-Carbon Based Carbon Nanotube Thin Film Transistors. (5th May 2020) - Li, Huaping; Zhou, Lili
Abstract : This work reports transfer curve characterization, capacitance-voltage measurement, bias stress test, bending and stretching tests of the high fidelity flexible and stretchable thin-film transistors constructed on unsorted single-walled carbon nanotubes drain-source-gate electrodes, sorted semiconducting single-walled carbon nanotubes thin film active layer, and nonpolar styrene−ethylene−butadiene−styrene (SEBS) hydrogenated elastomer dielectric and substrate. The air-stable, hysteresis-less, negligible threshold shift under bias stress test, stable performance during bending, and slightly current density changes under stretching strains of these all-carbon based thin-film transistors qualify for basic elements applicable in industrial flexible and stretchable electronics.